An Analysis of the Activators of Single-Chain Urokinase-Type Plasminogen Activator (scu-PA) in the Dextran Sulphate Euglobulin Fraction of Normal Plasma and of Plasmas Deficient in Factor XII and Prekallikrein - Binnema, D J; Dooijewaard, G; Turion, P N C (Thrombosis and Haemostasis, 1991)
An analysis was made of the various possible activators of single-chain urokinase-type plasminogen activator (scu-PA) in the dextran sulphate euglobulin fraction (DEF) of human plasma. scu-PA activators were detected in an assay system in which the substrate scu-PA, in physiological concentration (50 pM), was immuno-immobilized. After activation of the immobilized scu-PA for a certain period of time the activity of the generated amount of immuno-immobilized two-chain u-PA was determined with plasminogen and the chromogenic substrate S-2251. The scu-PA activator activity (scuPA-AA) in the DEF of plasmas deficient in factor XII or prekallikrein was about half of that in the DEF of normal plasma. Separation of scuPA-AA in the DEF by gel chromatography showed to major peaks, one eluting with an apparent Mr of 500,000 and the other around Mr 100,000. The former peak, which coincided with the activity peak of the kallikrein-kininogen complex, was absent in the DEF of plasma depleted of prekallikrein and therefore was identified as kalli-krein. The latter peak was still present in the depleted plasma and most likely represents plasmin, because its scuPA-AA coincided with the activity peak of plasmin and could be fully inhibited by antibodies raised against human plasminogen. It is concluded that plasmin and the contact-activation factor kallikrein each contribute for about 50% to the scuPA-AA in the DEF. Compared on a molar basis, however, plasmin was found to be almost 1,000 times more effective than kallikrein, and we conclude, therefore, that in vivo plasmin is the primary activator of scu-PA and the role of the contact system is of secondary importance.